Fatigue performance of high strength steel built-up box T-joints. (March 2015) - Chiew, S.P.; Zhao, M.S.; Lee, C.K.
Abstract: In this study, experiments were conducted to study the fatigue behaviors of two full scale high strength steel built-up box T-joints. Firstly, the stress concentration factors at the joint intersection were measured. Secondly, fatigue tests were conducted with the crack growth monitored by the Alternating Current Potential Drop micro-gauge. It is found that the fatigue resistance of the high strength steel joints could be conservatively predicted by the existing fatigue design curves for normal strength steels. In addition, the higher residual stress present in the joints seems to produce little effects on the crack penetration rate in the thickness direction. Highlights: The hot spot stress method can reliably predict the crack initiation position. Crack propagation behaviors of RQT-S690 are not much different from S355J2H. S–N curve predicted the fatigue life of high strength steel box joint conservatively. Residual stress shows little effect on the fatigue performance for joints tested.